Wagner discourse of contemporary philosophy: Alain Badiou vs Philip Lacou-Labarthe - Olena Karpenko (Cхід, 2016)
The article focuses on reconstructing the structures of implicit criticism on postmodern understanding of music, found within the discourse of a dispute between Alain Badiou and Philip Lacou-Labar the concerning philosophical interpretation of Richard Wagner's musical works. It was revealed that A. Badiou proposes a program to overcome the characteristic deconstructivist reduction of art to politics that brings the former to another by-product of ideology. Negative conceptual apparatus of deconstruction is opposed by A. Badiou with a hermeneutics, characterized by affirmative morphology and syntax constituted onto the pragmatics of a lesson, teaching action, open gesture of involvement. Badiou si an approach marks a good possibility of overcoming the methodological and ideological deadlock of postmodernity. This new wave of philosophical debates around Richard Wagner responds to the revival of grand epical genres in mass culture. Consequently a new dialectical thinking must be taught in order to continue the tradition of critical approach to culture. This is the key implication of A. Badiou's lessons on how it is possible to rethink the works of art and historically determined approaches to understanding them besides the clich?s of the recent postmodernist legacy. Although Badiou's critique itself can be seen as a kind of postmodernist interpreting technique, the French philosopher manages to escape the overt radicalism of postmodernist claims against Wagner by means of true radicalityof affirmative interpretation inspired not by suspicion of a concealed truth but rather a commitment to a truth to come.